TRANSFORMING TECHNICAL EDUCATION TOWARDS INDUSTRY NEEDS - Venkatesh, Koushick (Institute of Advanced Engineering and Science, 2020)
Technical education governs the maturity and socioeconomic circumstance of a nation. A sound professional training brings skilled human resources. Annually in India huge number of engineers graduates from over 4500 engineering colleges. But only 12 percent of those are employable. It indicates lack of employability skills rather than lack of opportunity. Current Indian education system focuses on scoring in an exam rather than gaining knowledge. Also, a discrepancy exists flanked by the education system, and the industry needs comprise old syllabi and weak interaction with industrialist. Memoranda of understanding (MoU) with industries, industrial training for faculties and students, effective regulation and monitoring by statutory organization like the All India Council for Technical Education (AICTE) and the University Grants Commission (UGC) might help in quality and employable graduates for the economic augmentation of our nation.